School of Anak Laut (Sea Children): Educational Philanthropy Movement in Bajo Community of Three-Coral World Center - Muhammad Alifuddin; Alhamuddin Alhamuddin; Nurjannah Nurjannah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This article provided an anlytical description of the Muhammadiyah philanthropic movement to the Bajo community in Wakatobi. There were three important points hacked in this study, namely: (1). Why did Muhammadiyah choose the domain of education for its philatropical movement in the Bajo community? (2). what was the pattern of Muhammadiyah's educational philanthropic movement in the Bajo community? (3). what was the Bajo community's response to the Muhammadiyah-based pure Islamic education philanthropy movement? Data collection was done through in-depth interviews, observation and documentation. Analyzing data used hermeneutic phenomenology approach. The results showed that the choice of moving in the realm of education by the local Muhammadiyah community was due to the essence of the education movement as a fulcrum for determining the quality of human resources, on the other hand expensive quality education services made most Bajo children to choose to go to sea rather than go to school. The choice of educational philanthrophy by Muhammadiyah was also due to the psycho-social reality of local children who were suspected of "experiencing" an inferiority complex when they interacted with the mainland children's community. The philanthropic movement pattern implemented by the local Muhammadiyah community was based on the philanthropic social movement, namely to form awareness of the local community about the urgency of education for future life continuity by relying on a belief system or religious basis. The smart work of the Muhammadiyah community combined with the positive action approach made the pure Islamic idea could be transformed into the Bajo cultural space through education and teaching in a natural humanistic manner, without causing controversy. Keywords: Educational Philanthrophy, Bajo Community, Educational Philanthrophy Movement